2014
DOI: 10.1111/jzs.12067
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of northern Dolly VardenSalvelinus malma malmabased on analysis of mitochondrial DNA

Abstract: The northern Dolly Varden, Salvelinus malma malma, is a typical representative of arctic fauna distributed in northeastern Asia and northwestern North America. Because its spawning habitats were affected by Pleistocene glacial advances over most of its natural range, S. m. malma is among the most interesting objects of phylogeographic and microevolutionary studies. We reconstructed the genealogy of mtDNA haplotypes from 27 Alaskan and Asian populations to study the influence of glacial and geological vicarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…This pattern is consistent with bottlenecks and founder effects in populations that postglacially colonized novel habitats as they became ice-free and, as such, harbour only a subset of the genetic variability of the source, refugial population(s) (Hewitt 1996;Provan and Bennett 2008). Assuming a Beringian origin for northern Dolly Varden (Oleinik et al 2013(Oleinik et al , 2014) and a stepping stone-like pattern of recolonization along coastal habitats as has been suggested for other fishes in the region (e.g., Wilson and Hebert 1998; but see Harris and Taylor 2010 for an alternative interior postglacial dispersal hypothesis), our results are consistent with the idea that Alaskan portions of Beringia served as the origin of contemporary populations of northern Dolly Varden and that historical factors have also been Table 1. important for driving the distribution of genetic variation in Northern Dolly Varden.…”
Section: Influences On Genetic Variationsupporting
confidence: 80%
See 2 more Smart Citations
“…This pattern is consistent with bottlenecks and founder effects in populations that postglacially colonized novel habitats as they became ice-free and, as such, harbour only a subset of the genetic variability of the source, refugial population(s) (Hewitt 1996;Provan and Bennett 2008). Assuming a Beringian origin for northern Dolly Varden (Oleinik et al 2013(Oleinik et al , 2014) and a stepping stone-like pattern of recolonization along coastal habitats as has been suggested for other fishes in the region (e.g., Wilson and Hebert 1998; but see Harris and Taylor 2010 for an alternative interior postglacial dispersal hypothesis), our results are consistent with the idea that Alaskan portions of Beringia served as the origin of contemporary populations of northern Dolly Varden and that historical factors have also been Table 1. important for driving the distribution of genetic variation in Northern Dolly Varden.…”
Section: Influences On Genetic Variationsupporting
confidence: 80%
“…Additionally, given that freshwater-resident northern Dolly Varden occur predominately as males, then gene flow between freshwaterresident and anadromous fish from the same system should be detectable. Finally, although contemporary gene flow is likely limited (or absent) between geographically distant populations and between those isolated above impassable barriers, we hypothesized that gene flow may have historically been high between all populations given the historical postglacial colonization of this region by one Beringian lineage (Oleinik et al 2013(Oleinik et al , 2014. To assess this hypothesis, the coalescent theory-based program MIGRATE-N (version 3.6; Beerli and Felsenstein 2001;Beerli 2006Beerli , 2009) was used to infer levels of historical gene flow among populations.…”
Section: Assessment Of Dispersal and Gene Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses of charrs throughout the northern coast of the Sea of Okhotsk revealed that all individuals from Lake Grand possessed S. malma malma mtDNA, and these results are consistent with published data (Gudkov & Radchenko, 2000;Osinov et al, 2018;Radchenko, 2003Radchenko, , 2004a. The divergence of mtDNA nucleotide sequences between the population from Lake Grand and the three populations of the Sea of Okhotsk coast was within the range of interspecific divergence for S. malma malma (Oleinik et al, 2014). On the other hand, Bayesian clustering and NJ tree based on msDNA indicated the genetic mixture of the two mtDNA lineages in the Yama River-Lake Grand basin.…”
Section: Re Sultssupporting
confidence: 91%
“…The divergence of mtDNA nucleotide sequences between the population from Lake Grand and the three populations of the Sea of Okhotsk coast was within the range of interspecific divergence for S . malma malma (Oleinik et al, 2014). On the other hand, Bayesian clustering and NJ tree based on msDNA indicated the genetic mixture of the two mtDNA lineages in the Yama River–Lake Grand basin.…”
Section: Discussionmentioning
confidence: 99%